The neoliberal system and the Força Sindical - Graciolli, Edilson José (FCL-UNESP Laboratório Editorial, 2007)
This text analyses the relation between the neoliberal system and the participative union, more precisely the Força Sindical, as a necessary condition for the understanding of the change in the idealistic orientation of the Metallurgic Union of Volta Redonda since1992, when its command began to act in accordance with the Força Sindical against its previous labor combativeness present among those workers from 1983 to 1991. In this context, not only the neoliberal reasons for the unionism but also the elements of the Força Sindical ideas which belong to the world vision of this project are discussed.